Spatial correlation between coastal distance and pyrite pH in acid sulfate soils of Paser, East Kalimantan - Setianingsih, Titin Eka; Bagus Adi Nugroho; Raden Mas Nurhartanto; Zulkarnain, Zulkarnain (Journal of Degraded and Mining Lands Management, 2026)
Acid sulfate soils derived from marine or tidal swamp sediments containing pyrite (FeS?) pose major challenges to agricultural productivity due to their tendency to generate sulfuric acid upon oxidation. The soils are widely distributed in tropical lowland paddy fields and constitute a significant constraint to both soil fertility and crop yields. This study aimed to investigate the spatial correlation between coastal distance and pyrite-related soil acidity in paddy fields of Paser Regency, East Kalimantan, Indonesia. Soil samples collected from twelve sampling sites in Tanah Grogot and Long Kali Subdistricts were analyzed for initial pH and pH after hydrogen peroxide oxidation. The distances to the coastline were measured using ArcGIS Pro. The results showed that ?pH values ranged from 2.2 to 4.4, with the highest value recorded in Muara Telake (?pH = 4.4, 2.18 km from the coastline). Statistical analysis revealed a significant negative correlation between ?pH and distance from the coast (r = -0.50, p<0.05). Regression analysis further indicated that each unit increase in ?pH corresponded to a reduction of approximately        3.01 km in coastal distance. This study highlighted ?pH as a reliable indicator for identifying potential acid sulfate soil risk zones, particularly in paddy fields within 5 km of the coastline. By integrating soil acidity indicators with lime requirement estimates, the study also identified the potential of coal fly ash (CFA) as a cost-effective amendment to mitigate acidity and improve soil fertility.